Beyond Branding: The Dominant Role of Tourist Attractions and Digital Promotion in Driving International Revisit Intentions to Nusa Dua, Bali - Dayan Hakim Natigor Sihaputar; Ekos Albar; Irfani Fithria; Listri Herlina (International Journal of Business, Management and Economics, 2026)
Nusa Dua, Bali, is an integrated tourism area in South Bali, known for its international standards, luxury resorts, and a 4 km stretch of white-sand beach. The destination is also recognized for its sustainable tourism, having been designated an environmentally friendly "Green Zone Destination." This study aims to analyze the effects of Branding Strategy, Tourist Attractions, and Digital Promotion on the Decision to Revisit Nusa Dua, Bali, among foreign tourists. The research was conducted on 385 foreign visitors who stayed in the Nusa Dua area between December 24, 2025, and January 2, 2026. The results indicate that Branding Strategy, Tourist Attractions, and Digital Promotion each have a positive and significant influence, both partially and simultaneously, on the Decision to revisit the Nusa Dua area. Of all the independent variables, Tourist Attractions is the most dominant factor influencing the decision to revisit, with the largest positive regression coefficient.